Mechanical Thrombectomy in Patients With Ischemic Stroke With Prestroke Disability. Issue 5 (May 2020) - Salwi, Sanjana; Cutting, Shawna; Salgado, Alan D.; Espaillat, Kiersten; Fusco, Matthew R.; Froehler, Michael T.; Chitale, Rohan V.; Kirshner, Howard; Schrag, Matthew; Jasne, Adam; Burton, Tina; MacGrory, Brian; et al.
Abstract : Background and Purpose—: We aimed to compare functional and procedural outcomes of patients with acute ischemic stroke with none-to-minimal (modified Rankin Scale [mRS] score, 0–1) and moderate (mRS score, 2–3) prestroke disability treated with mechanical thrombectomy. Methods—: Consecutive adult patients undergoing mechanical thrombectomy for an anterior circulation stroke were prospectively identified at 2 comprehensive stroke centers from 2012 to 2018. Procedural and 90-day functional outcomes were compared among patients with prestroke mRS scores 0 to 1 and 2 to 3 using χ 2, logistic, and linear regression tests. Primary outcome and significant differences in secondary outcomes were adjusted for prespecified covariates. Results—: Of 919 patients treated with mechanical thrombectomy, 761 were included and 259 (34%) patients had moderate prestroke disability. Ninety-day mRS score 0 to 1 or no worsening of prestroke mRS was observed in 36.7% and 26.7% of patients with no-to-minimal and moderate prestroke disability, respectively (odds ratio, 0.63 [0.45–0.88], P =0.008; adjusted odds ratio, 0.90 [0.60–1.35], P =0.6). No increase in the disability at 90 days was observed in 22.4% and 26.7%, respectively. Rate of symptomatic intracerebral hemorrhage (7.3% versus 6.2%, P =0.65), successful recanalization (86.7% versus 83.8%, P =0.33), and median length of hospital stay (5 versus 5 days, P =0.06) were not significantly different. Death by 90 days was higher in patients with moderate prestroke disability (14.3% versus 40.3%; odds ratio, 4.06 [2.82–5.86], P <0.001; adjusted odds ratio, 2.83 [1.84, 4.37], P <0.001). Conclusions—: One-third of patients undergoing mechanical thrombectomy had a moderate prestroke disability. There was insufficient evidence that functional and procedural outcomes were different between patients with no-to-minimal and moderate prestroke disability. Patients with prestroke disability were more likely to die by 90 days. Abstract : Supplemental Digital Content is available in the text.